2021 ISFM Consensus Guidelines on the Collection and Administration of Blood and Blood Products in Cats. Issue 5 (May 2021) - Taylor, Samantha; Spada, Eva; Callan, Mary Beth; Korman, Rachel; Leister, Ellie; Steagall, Paulo; Lobetti, Remo; Seth, Mayank; Tasker, Séverine
Practical relevance: Blood and blood products are increasingly available for practitioners to use in the management of haematological conditions, and can be lifesaving and therapeutically useful for patients with anaemia and/or coagulopathies. It is important for feline healthcare that donors are selected appropriately, and transfusions of blood or blood products are given to recipients that will benefit from them. Complications can occur, but can be largely avoided with careful donor management and recipient selection, understanding of blood type compatibility, and transfusion monitoring. Clinical challenges: Feline blood transfusion, while potentially a lifesaving procedure, can also be detrimental to donor and recipient without precautions. Cats have naturally occurring alloantibodies to red cell antigens and severe reactions can occur with type-mismatched transfusions. Blood transfusions can also transmit infectious agents to the recipient, so donor testing is essential. Finally, donors must be in good health, and sedated as appropriate, with blood collected in a safe and sterile fashion to optimise the benefit to recipients. Transfusion reactions are possible and can be mild to severe in nature. Autologous blood transfusions and xenotransfusions may be considered in certain situations. Evidence base: These Guidelines have been created by a panel of authors convened by the International Society of Feline Medicine (ISFM), based on available literature. They are aimed at general practitioners to provide a practical guide to blood typing, cross-matching, and blood collection and administration.